Structural variations in livestock genomes and their associations with phenotypic traits: a review - Chen, Yinghui; Khan, Muhammad Zahoor; Wang, Xinrui; Liang, Huili; Ren, Wei; Kou, Xiyan; Liu, Xiaotong; Chen, Wenting; Peng, Yongdong; Wang, Changfa (Frontiers in Veterinary Science, 2024)
Genomic structural variation (SV) refers to differences in gene sequences between individuals on a genomic scale. It is widely distributed in the genome, primarily in the form of insertions, deletions, duplications, inversions, and translocations. Due to its characterization by long segments and large coverage, SVs significantly impact the genetic characteristics and production performance of livestock, playing a crucial role in studying breed diversity, biological evolution, and disease correlation. Research on SVs contributes to an enhanced understanding of chromosome function and genetic characteristics and is important for understanding hereditary diseases mechanisms. In this article, we review the concept, classification, main formation mechanisms, detection methods, and advancement of research on SVs in the genomes of cattle, buffalo, equine, sheep, and goats, aiming to reveal the genetic basis of differences in phenotypic traits and adaptive genetic mechanisms through genomic research, which will provide a theoretical basis for better understanding and utilizing the genetic resources of herbivorous livestock.